PENGARUH REWARD TERHADAP KINERJA KARYAWAN PADA CV YAMAHA SURYA PRIMA TANJUNG TABALONG (p3m.stiatabalong.ac.id, 2022)
The aims of this study were (1) to find out and analyze the effect of rewards on employee performance at CV Yamaha Surya Prima Tanjung Tabalong (2) to analyze how much influence rewards have on employee performance at CV Yamaha Surya Prima Tanjung Tabalong. Research using quantitative methods. The research was conducted at the CV Yamaha Surya Prima Tanjung Tabalong office. The overall population at CV Yamaha Surya Prima Tanjung Tabalong is less than 100 people, namely 37 employees, so all populations are taken for this study. The research sample in this study used a probability sampling technique, namely a sampling technique that provides equal opportunities for each member of the population. The total population in the CV Yamaha Surya Prima Tanjung Tabalong office is 37 employees so all populations are used in this study sample, namely 37 employee respondents at CV Yamaha Surya Prima Tanjung Tabalong with the main criteria being employees at the CV Yamaha Surya Prima Tanjung Tabalong office. Data analysis using the Gesca Offline program uses a significance level of 5%, so if it does not meet the significance level, the hypothesis is rejected. The results showed (1) There was an effect of reward on employee performance at CV Yamaha Surya Prima Tanjung Tabalong (2) The magnitude of the effect of reward on employee performance at CV Yamaha Surya Prima Tanjung Tabalong was 49.7% and the remaining 50.3% was influenced by factors outside this study. Keywords: Employee Reward and Performance